Manpower Planning Model For Pilot Accessions In The Royal Malaysian Air Force - M. Jamil, Khairron Anuar (1994)
This research aims to evaluate recruitment policies via mathematical model to project the strength of RMAF pilots for more than ten years. Previous researches have adopted the weighted Linear Goal Programming (LGP) technique to evaluate recruitment policies, however a preemptive LGP technique is used in this research. This technique has some advantages over the weighted LGP technique.